Management of biological waste of patients after radionuclide therapy - L. A. Chipiga; A. V. Vodovatov; I. A. Zvonova; A. A. Stanzhevsky; A. V. Petryakova; E. E. Anokina; K. S. Velichkina; S. A. Ryzhov (Радиационная гигиена)
Radioactive waste management is a modern-day issue in terms of radiation safety due to the development of radionuclide therapy, the emergence of new radiopharmaceuticals, radionuclides, and treatment methods, which allow for radionuclide therapy in a day hospital. According to the current domestic regulatory and methodological support biological wastes generated during the patient’s metabolic activity after injection of the radiopharmaceuticals for the therapy refer to the liquid radioactive waste. These wastes must be collected and kept for decay in hospitals to the safe levels before being spilled into the municipal sewerage. It requires additional expenses to the hospital for making the special sewerage. To increase the availability of radionuclide therapy, it is necessary to update the requirements of the liquid radioactive waste management in nuclear medicine departments, considering the volume activities of different diagnostic and therapeutic radionuclides in wastes generated after the injection of radiopharmaceuticals to the patients. On the basis of findings, it is possible to evaluate the feasibility of the binding requirement for the availability of special sewerage in the departments of the radionuclide therapy. In this work, excretion of the radiopharmaceuticals used in therapy: 89Sr-dichloride, 223Ra-dichloride, 131I-MIBG, 177Lu-PSMA, and 225Ac-PSMA was studied based on published data to determine the activity levels of radionuclides in waste of patients. As a results of preliminary computations, some nuclear medicine procedure will not lead to generation of liquid radioactive waste from biological waste of patients in sewerage system in usual operating condition and special sewerage is not strictly necessary. For example, estimations of radionuclide activity in wastes showed the volume of current sewerage system in a small hospital with a limitation of 50 beds can be enough to reduce the level of specific activity of radionuclides in wastewater from one patient a day after radionuclide therapy with 89Sr-chloride and 223Ra-dichloride. In order to revision of requirements to special sewerage in each department of radionuclide therapy and to development of differentiated approach to the management of biological waste of patient in nuclear medicine departments, which ensure environment protection and radiation safety of people, it is necessary to continue the research including development and modeling of realistic scenario of staff and patient radiation exposure confirmed experimental results.